Geographical constraints are stronger than invasion patterns for European urban floras. - Carlo Ricotta (PLoS ONE, 2014)
Understanding the mechanisms that affect invasion success of alien species is an important prerequisite for the effective management of present and future aliens. To gain insight into this matter we asked the following questions: Are the geographical patterns of species distributions in urban floras different for native compared with alien plant species? Does the introduction of alien species contribute to the homogenization of urban floras? We used a Mantel test on Jaccard dissimilarity matrices of 30 urban floras across the British Isles, Italy and central Europe to compare the spatial distribution of native species with four classes of alien species: archaeophytes, all neophytes, non-invasive neophytes, and invasive neophytes. Archaeophytes and neophytes are species that were introduced into Europe before and after 1500 AD, respectively. To analyze the homogenizing effect of alien species on the native urban floras, we tested for differences in the average dissimilarity of individual cities from their group centroid in ordination space. Our results show that the compositional patterns of native and alien species seem to respond to the same environmental drivers, such that all four classes of alien species were significantly related to native species across urban floras. In this framework, alien species may have an impact on biogeographic patterns of urban floras in ways that reflect their history of introduction and expansion: archaeophytes and invasive neophytes tended to homogenize, while non-invasive neophytes tended to differentiate urban floras.